MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI BERMAIN LEMPAR TANGKAP BOLA PADA ANAK USIA 5-6 TAHUN DI PAUD AMANAH KECAMATAN BANGKINANG KABUPATEN KAMPAR - Salmah Salmah; Zulkifli Zulkifli; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase in gross motor skills in group B children through play catch the ball in the Early Childhood Education Amanah District Bangkinang Regency Of Kampar .This research is a type of research that use or classroom action research (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children in group B which has 15 children in early childhood Amanah. The research data obtained through observation and data analysis were conducted by using descriptive analysis of quantitative and qualitative. The results showed that throwing playing catch ball can improve gross motor skills in children in group B. It can be seen from the increase in the average percentage of gross motor skills of children in the first cycle of 50.83%, which is in the category fairly and increased by 40% in the second cycle into 73.20% which are in both categories. So, play catch ball throwing d apat improve gross motor skills at 5-6 years old children in early childhood Amanah Bangkinang District of Kampar regency.Keywords : Gross Motor Skill, Play Catch The Ball